Validity, reliability, and factor analysis of organoleptic tests of Dangke Deppamil as an alternative treatment of nutrition problems in pregnant women in Indonesia - Hidayanti Arifuddin; Rosa Dwi Wahyuni; Hikmayanti Arifuddin; A Fahira Nur; Adhar Arifuddin (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Dangke is a traditional food product sourced from high-quality cow's milk from Enrekang Regency, South Sulawesi, Indonesia. The nutrients contained in Dangke are a source of calories needed by the body and can help meet the nutritional needs of pregnant women. The present study was conducted to validate the organoleptic instrument of Deppamil Dangke through validity, reliability, and factor analysis; the organoleptic test of Deppamil Dangke was carried out. MATERIALS AND METHODS: This type of research is a mix method with an explanatory sequential design approach. Qualitative analysis was done using Atlas Ti software. RESULTS: The results of the instrument validation showed a reliable level of instrument validity with Kaiser-Meyer-Olkin results (0.747), and the Cronbach's coefficient alpha values of each of the two types of Deppamil Dangke were 0.84 and 0.91. Exploratory factor analysis identified two main factors using the varimax rotation and excluded items with a factor loading below 0.3, which included taste (2 items), color (2 items), aroma (2 items), and texture (2 items), which explains 52.7% of the general variance of the Deppamil Dangke organoleptic test. The confirmatory factor analysis results showed that the factor structure of the Deppamil Dangke organoleptic instrument matched the data (CFI = 0.948, TLI = 0.936, RMSEA = 0.069, and WRMSR = 0.891). The factor loading of the model ranged from 0.691 to 0.825 and was statistically significant. The organoleptic test results of the Deppamil Dangke on 30 panelists of pregnant women showed that pregnant women really liked the taste as much as 63.3%, texture as much as 53.3%, and color as much as 50%, and those who really liked the aroma were as much as 46.7%. CONCLUSION: Recommendation: Deppamil Dangke is liked by pregnant women and is very suitable to be used as an additional food product for pregnant women. It is necessary to make changes and innovations from the Dangke Deppamil product in terms of both texture and appearance and especially in the variety of flavors so that pregnant women can choose flavors according to their wishes and needs.